Model science teacher preparation programs : an international comparison of what works - Pedersen, Jon E., 1960-; Isozaki, Tetsuo; Hirano, Toshihde (Emerald Publishing Limited : Information Age Publishing, Inc., 2017)
This volume will focus on a much need comparison of science teacher preparation from around the world. In recent times (last 5 years) much has been written and communicated both in the popular press and within the annals of research oriented publications about the performance of students international in math and science. Although not a new discussion or debate, many countries are held as exemplars in how they educate their youth and subsequently how they educate their teachers. Given this situation and given the fact that there is ample evidence to show that some countries youth perform better on tests such as the Program for International Student Assessment (PISA) and we know that teacher significantly contribute to the performance of students, it is time that we look at the specific attributes of teacher preparation worldwide.Although this volume will not look at every country that is in the comparator group for PISA and other measures, we have contacted over 18 potential authors in the same number of countries in which there is ample evidence to show successes regarding student performance and quality teacher preparation programs. The intent of the book is not just to report on the "success" of each nation. Rather the intent is to ask authors to take a critical look at the process by which science teachers are educated and share with the reader both the positive and negative aspects of such preparation programs. For all 15 contributed chapters, the editors have analyzed each and from this constructed from the "data" an analysis and report in a final chapter on the exemplary qualities from various nations and make specific recommendations regarding science teacher preparation for the global community.